Empowering students: a campaign to combat fake news through literacy education - Eros Meilina Sofa; Ahmad Burhanuddin; Mislina (Erudita: Journal of English Language Teaching, 2025)
Fake news has become widely consumed by society in all circles, dealing with the intentions and dangers. This study investigates how students identify fake news and educate the community on its circulation. This study employed a qualitative approach and a descriptive qualitative design. It investigated the fake news found, how to identify it, and how to educate others about fake news. This study recruited sixty-four participants, comprising students who had been educated on the characteristics of fake news and critical reading skills. To collect the data, this study used a questionnaire and interviews. The identification of fake news included several steps, which depend on the character and form of the news itself. These steps began with identifying the image or appearance of the news itself and then examining the sentence patterns used by the news to persuade readers to believe it. In addition, they were also willing and able to educate other people not to believe fake news easily. They took several steps, including educating people on how to identify the date of publication and checking the source. This study provided practical information about the steps involved in identifying and educating people about the widespread dissemination of fake news.